Is pelvic vein incompetence associated with symptoms of chronic pelvic pain in women? A pilot study. (January 2016) - Hansrani, Vivak; Morris, Julie; Caress, Ann-Louise; Payne, Katherine; Seif, Mourad; McCollum, Charles N.
Abstract: Objective: Pelvic vein incompetence (PVI) affects 15–20% of all women, yet we know little about how it affects sufferers. The aim of this prospective pilot study was to explore symptoms experienced by women with PVI, and determine its impact on quality of life and NHS costs. Study design: Case-control study at a UK University teaching hospital conducted over an eight-month period. Cases were 40 premenopausal women aged 18–49 years with PVI and varicose veins (VV). There were two age-matched controls groups: (i) 40 healthy women with no PVI but with VV, and (ii) 40 healthy women with no PVI and no VV. Subjects were asked to complete a structured questionnaire on disease specific outcomes, health status and use of healthcare resources. Results: Mean age (range) was 39.8 (24–47) years for cases, 39.1 (24–49) for VV controls and 38 (25–49) for healthy controls. Pelvic pain was reported by 38 of 40 (95%) PVI cases, compared with 25 of 40 (62%) VV controls, and 26 of 40 (65%) healthy controls ( p = 0.001). The median (range) EQ-5D utility score for PVI cases was 0.80 (0.29–1.0) compared with 0.80 (0.09–1.0) for VV controls and 1.0 (0.62–1.0) for healthy controls ( p = 0.002). Of the 40 PVI cases, 35 (88%) visited a consultant in the previous 12 months compared with 12 of 40 (30%) VV controls, and 14 of 40 (35%) healthy controls ( p < 0.001). Conclusions: Women with PVI report a greater frequency of pelvic pain with reduced health status and increased use of healthcare resources compared with matched controls.